If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = 6x + -10 Reorder the terms: 8 + 3x = 6x + -10 Reorder the terms: 8 + 3x = -10 + 6x Solving 8 + 3x = -10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 8 + 3x + -6x = -10 + 6x + -6x Combine like terms: 3x + -6x = -3x 8 + -3x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 8 + -3x = -10 + 0 8 + -3x = -10 Add '-8' to each side of the equation. 8 + -8 + -3x = -10 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = -10 + -8 -3x = -10 + -8 Combine like terms: -10 + -8 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 8y-3=57+12 | | 5n+34=-2(17n) | | 4(2x-3)=6x-20 | | -6x-2+7x=8 | | -19=-3x-4x+9 | | 7x^2-800x+10000=0 | | (x+1)(5x-5)=-98 | | (x-5)(5x+1)=-5 | | 8a+5b+2b-5a= | | 66-7x=11x+18 | | x*2-5=3 | | 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 |